Warming and Nitrogen Addition Alter Photosynthetic Pigments, Sugars and Nutrients in a Temperate Meadow Ecosystem - Zhang, Tao (PLoS One, 2016)
Global warming and nitrogen (N) deposition have an important influence on terrestrial ecosystems; however, the influence of warming and N deposition on plant photosynthetic products and nutrient cycling in plants is not well understood. We examined the effects of 3 years of warming and N addition on the plant photosynthetic products, foliar chemistry and stoichiometric ratios of two dominant species, i.e., Leymus chinensis and Phragmites communis, in a temperate meadow in northeastern China. Warming significantly increased the chlorophyll content and soluble sugars in L. chinensis but had no impact on the carotenoid and fructose contents. N addition caused a significant increase in the carotenoid and fructose contents. Warming and N addition had little impact on the photosynthetic products of P. communis. Warming caused significant decreases in the N and phosphorus (P) concentrations and significantly increased the carbon (C):P and N:P ratios of L. chinensis, but not the C concentration or the C:N ratio. N addition significantly increased the N concentration, C:P and N:P ratios, but significantly reduced the C:N ratio of L. chinensis. Warming significantly increased P. communis C and P concentrations, and the C:N and C:P ratios, whereas N addition increased the C, N and P concentrations but had no impact on the stoichiometric variables. This study suggests that both warming and N addition have direct impacts on plant photosynthates and elemental stoichiometry, which may play a vital role in plant-mediated biogeochemical cycling in temperate meadow ecosystems.